Dielectric characterization of thermally aged recycled Polyethylene Terephthalate and Polyethylene Naphthalate reinforced with inorganic fillers. Issue 5 (4th May 2017) - Mebarki, Fouzia; David, Eric
Abstract : In order to assess the influence of the operating temperature on the dielectric properties of recycled Polyethylene Terephthalate (PET) and Polyethylene Naphthalate (PEN) reinforced with inorganic fillers, a dielectric and thermal investigation was undertaken. Specimens were thermally aged at several temperatures between 90 and 200°C for 360 h. The effect of thermal aging time on dielectric and thermal properties was also investigated. The dielectric response and breakdown strength properties were evaluated. Differential scanning calorimetry (DSC) measurements showed that the degree of crystallinity and the glass transition temperature increased with aging temperature and duration. The data obtained showed that these materials exhibited a good resistance to thermal aging at temperatures below 140°C. Furthermore, it was found that the dielectric strength of the recycled PET and PEN and their composites decreased considerably for temperatures of over 170°C. POLYM. ENG. SCI., 2017. © 2017 Society of Plastics Engineers